A reader's guide to the evaluation of screening studies. Issue 844 (February 1996) - Earle, C.; Hebert, P. C.
Abstract : In this article we will review how a reader should evaluate a screening study. A clinical problem involving screening mammography is presented. We then outline criteria to determine whether screening is appropriate for a given condition. A search for relevant articles is described followed by an outline of the steps used to appraise a screening study critically. An applicable study is examined in detail for such things as the quality of randomisation and outcomes measured. The results of this study are then applied to a patient considered for screening.